Tissue plasminogen activator followed by antioxidant-loaded nanoparticle delivery promotes activation/mobilization of progenitor cells in infarcted rat brain. (March 2016) - Petro, Marianne; Jaffer, Hayder; Yang, Jun; Kabu, Shushi; Morris, Viola B.; Labhasetwar, Vinod
Abstract: Inherent neuronal and circulating progenitor cells play important roles in facilitating neuronal and functional recovery post stroke. However, this endogenous repair process is rather limited, primarily due to unfavorable conditions in the infarcted brain involving reactive oxygen species (ROS)-mediated oxidative stress and inflammation following ischemia/reperfusion injury. We hypothesized that during reperfusion, effective delivery of antioxidants to ischemic brain would create an environment without such oxidative stress and inflammation, thus promoting activation and mobilization of progenitor cells in the infarcted brain. We administered recombinant human tissue-type plasminogen activator (tPA) via carotid artery at 3 h post stroke in a thromboembolic rat model, followed by sequential administration of the antioxidants catalase (CAT) and superoxide dismutase (SOD), encapsulated in biodegradable nanoparticles (nano-CAT/SOD). Brains were harvested at 48 h post stroke for immunohistochemical analysis. Ipsilateral brain slices from animals that had received tPA + nano-CAT/SOD showed a widespread distribution of glial fibrillary acidic protein-positive cells (with morphology resembling radial glia-like neural precursor cells) and nestin-positive cells (indicating the presence of immature neurons); such cells were considerably fewer in untreated animals or those treated with tPA alone. Brain sections from animals receiving tPA + nano-CAT/SOD also showed much greater numbers of SOX2- and nestin-positive progenitor cells migrating from subventricular zone of the lateral ventricle and entering the rostral migratory stream than in t-PA alone treated group or untreated control. Further, animals treated with tPA + nano-CAT/SOD showed far fewer caspase-positive cells and fewer neutrophils than did other groups, as well as an inhibition of hippocampal swelling. These results suggest that the antioxidants mitigated the inflammatory response, protected neuronal cells from undergoing apoptosis, and inhibited edema formation by protecting the blood–brain barrier from ROS-mediated reperfusion injury. A longer-term study would enable us to determine if our approach would assist progenitor cells to undergo neurogenesis and to facilitate neurological and functional recovery following stroke and reperfusion injury.